A Qualitative Study of Antibiotic Use Practices in Intensive Small-Scale Farming in Urban and Peri-Urban Blantyre, Malawi: Implications for Antimicrobial Resistance - Mankhomwa, John; Tolhurst, Rachel; M'biya, Eunice; Chikowe, Ibrahim; Banda, Pemphero; Mussa, Jimmy; Mwasikakata, Henry; Simpson, Victoria; Feasey, Nicholas; MacPherson, Eleanor E. (Frontiers in Veterinary Science, 2022)
The routine use of antimicrobials in meat production has been identified as a driver of antimicrobial resistance (AMR) in both animals and humans. Significant knowledge gaps exist on antibiotic use practices in farming, particularly in sub-Saharan Africa. This paper sought to generate in-depth understanding of household antibiotic use practices in food animals in urban- and peri-urban Blantyre. We used a qualitative research methodology focusing on households that kept scavenging animals and those engaged in small-scale intensive farming of food animals. Methods used were: medicine-use surveys with 130 conducted with a range of households; in-depth interviews (32) with a range of participants including farmers, community based veterinary health workers and veterinary shop workers; and stakeholder interviews (17) with policy makers, regulators, and academics. Six months of ethnographic fieldwork was also undertaken, with households engaged in farming, veterinary officers and veterinary stores. Our findings suggest antibiotic use in animals was more common in households that used small-scale intensive farming techniques, but rare in households that did not. For farmers engaged in small-scale intensive farming, antibiotics were often considered vital to remain solvent in a precarious economic and social environment, with limited access to veterinary services. A complex regulatory framework governed the import, prescription, and administration of antibiotics. Veterinary stores provided easy access to antibiotics, including colistin, an antibiotic on the WHO's critically important antibiotics for human health. Our work suggests that the high dependence on antibiotics for small-scale intensive farming may contribute to the growth of drug resistant infections in Malawi. The socio-economic drivers of antibiotic use mean that interventions need to take a holistic approach to address the high dependence on antibiotics. Key interventions could include improving farmers' access to affordable veterinary services, providing information about appropriate antibiotic use including withdrawal periods and feed supplementation, as well as improvements in regulation (nationally and internationally) and enforcement of current regulations. Taken together these approaches could lead to antibiotic use being optimised in feed animals.